Bacterial isolates and their antibiotic sensitivity pattern of surgical site infections among the surgical ward patients of Asella Referral and Teaching Hospital - Teshome Gebissa; Bonge Bude; Mohd Yasir; Shimelis Mekit; K. M. Noorulla (SpringerOpen, 2021)
Abstract Background Surgical site infection (SSI) is the most typical problem for patients who undergo operative procedures. It remains a typical and widespread problem causing morbidity and mortality, partly related to a rise in infections due to antimicrobial-resistant bacterial pathogens. The study was purposed to evaluate the bacterial isolates and their drug susceptibility patterns in patients with postoperative surgical site infection. Results The rate of postoperative surgical site infections was studied at Asella Referral and Teaching Hospital and found to be 23.3%. One hundred fifty specimens of pus and surface swabs were collected from the surgical site-infected patients over the period of March 2016 to May 2017, and from that, a total of 147 bacterial pathogens were recovered. The predominant organisms associated with postoperative surgical site infections were Klebsiella species 38 (26%, n=147), Escherichia coli 31 (21%, n=147), Staphylococcus aureus 25 (17%, n=147), and Pseudomonas aeruginosa 18 (12%, n=147). Conclusion Higher number of bacterial isolates were recovered. The predominant isolates were Klebsiella species, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The majority of gram-negative bacterial species which were isolated were found to be resistant to the commonly prescribed antimicrobial agents in the study setting. Thus, to achieve effective therapy for wound infections and to reduce/stop the appearance of multidrug-resistant (MDR) pathogens, continuous monitoring is essential with the fair use of antimicrobial agents.